Ecological aesthesis: figurations of the animal spirit in contemporary science, philosophy and literature - Carstens, Delphi (Religion, 2023)
Deborah Bird Rose uses the Aboriginal Yol’ngu term bir’yun – shimmer – to describe the inherent capacity to experience nature’s ancestral and ongoing power (2022). Using Rose’s concept as a leitmotif, this article investigates contemporary figurations of the animal spirit as it moves through the margins of contemporary science, philosophy, and literature. Using becoming figurations like sympoiesis, Gaia, the holobiont, and the Body without Organs (BwO), my argument is underpinned by Deleuze and Guattari’s (1987) philosophical attempts to subvert the dogmatic anthropocentric image of thought via becoming-animal/becoming-intense concepts. Beginning with an exploration of how science is beginning to overturn its own mechanistic view of the animal via new figurations of the animal assemblage, the article turns to a literary example – Robert Holdstock’s Lavondyss (1988) – to examine how we might go about addressing the nature of the becoming-animal assemblage to recapture the experience of shimmer as an ecologically aesthetic praxis.